Domestic and International Pilates Research Trends: A Review of Literature in Natural Science - Byoung-Jae Park; Se-Young Seon; So-Mi Yun (Asian Society of Kinesiology, 2023)
PURPOSE This study was conducted for the purpose of exploring the direction and quality of Pilates research in the future by comparing and analyzing research trends in the field of Pilates natural science at home and abroad. METHODS In order to analyze domestic and foreign Pilates research trends, we analyzed academic papers of the last 10 years (2013-2022) in the natural science field, and domestic papers were used as the keyword 'Pilates' using DP Pia, Kiss, and Riss, which are academic information services. A total of 105 papers were used by searching. For overseas studies, Pub med and Scholar were used, and only SCI and SCIE papers were collected and 129 papers were searched. RESULTS First, according to the comparative analysis of research trends by domestic and foreign fields, physiology (61%), kinematics (24.8%), and rehabilitation (14.2%) were found in the order of domestic, whereas in foreign countries, kinematics (34.9%) and physiology (33.3%) and rehabilitation (31.8%), a study with a relatively even distribution was conducted. Second, in the comparative analysis by study subject, domestic literature was the highest with 68.7% of studies targeting women, and was conducted separately by various age groups. Foreign fields, 40.9% of studies conducted by gender were found, and there were many studies that considered the characteristics of musculoskeletal disorders and metabolic diseases rather than gender. Third, looking at the comparison by research variable, studies have been conducted on various topics in physiology and kinetic dynamics. However, while domestic studies have focused on changes in body composition, foreign studies are actively conducting research on muscle function, musculoskeletal disorders, and rehabilitation. CONCLUSIONS In summary, it is judged that active research in the field of kinematics and rehabilitation should be conducted for more diverse subjects in the field of Pilates.